2008
DOI: 10.1097/iae.0b013e318162d982
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab (Avastin) Treatment of Retinal Angiomatous Proliferation

Abstract: These short-term data suggest that bevacizumab is a viable treatment option for RAP in AMD. The initial treatment effect appears to be maintained for at least 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
2
25
0
2
Order By: Relevance
“…Ghazi et al (2008) also reported their short-term experience with intravitreal bevacizumab of RAP. They found stabilization of visual acuity and central retinal thickness after a single injection for at least 8 weeks, suggesting that an injection frequency of less than one per month may be sufficient (Ghazi et al 2008). Wolf et al (2008) retrospectively evaluated 82 eyes with RAP treated with intravitreal bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghazi et al (2008) also reported their short-term experience with intravitreal bevacizumab of RAP. They found stabilization of visual acuity and central retinal thickness after a single injection for at least 8 weeks, suggesting that an injection frequency of less than one per month may be sufficient (Ghazi et al 2008). Wolf et al (2008) retrospectively evaluated 82 eyes with RAP treated with intravitreal bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, promising results with off-label intravitreal bevacizumab have been reported (Joeres et al 2007;Meyerle et al 2007;Ghazi et al 2008). Combined intravitreal bevacizumab and PDT for RAP had a positive effect on RAP lesions (Saito et al 2008 (Lai et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Only with introduction of anti-vascular endothelial growth factor drugs (VEGF) the results are slightly more promising, both with Bevacizumab (Avastin ® ) [21][22][23] and Ranibizumab (Lucentis ® ) [24]. Still, RAP seems to be an aggressive form of neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…They show favourable outcomes but frequent intravitreal injections are expected. [13][14][15][16] A combination therapy of bevacizumab and PDT has been hypothesized as being promising for neovascular ARMD, especially by prolonging the intervals between repeated injections. 17 Recent reports seem to confirm that combined intravitreal bevacizumab and PDT effectively maintained or improved visual acuity also for RAP lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Reductions of leakage, significant decrease in macular thickness and improvement or stabilization of visual acuity in about 90% of treated eyes were the common findings at the end of the follow-up. However, 30-50% of the treated eyes needed re-injection of bevacizumab within 3 months [13][14][15] and 70% after the 3 monthly scheduled injections. 16 Persistent lesion activity was noted in nearly all patients at the end of follow-up.…”
mentioning
confidence: 99%